2013
DOI: 10.1128/iai.00353-13
|View full text |Cite|
|
Sign up to set email alerts
|

The Bordetella pertussis Type III Secretion System Tip Complex Protein Bsp22 Is Not a Protective Antigen and Fails To Elicit Serum Antibody Responses during Infection of Humans and Mice

Abstract: bThe type III secretion system (T3SS) of pathogenic bordetellae employs a self-associating tip complex protein Bsp22. This protein is immunogenic during infections by Bordetella bronchiseptica and could be used as a protective antigen to immunize mice against B. bronchiseptica challenge. Since low-passage clinical isolates of the human pathogen Bordetella pertussis produce a highly homologous Bsp22 protein (97% homology), we examined its vaccine and diagnostic potential. No Bsp22-specific antibodies were, howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
0
15
0
1
Order By: Relevance
“…An additional key aspect to consider is the potential endotoxin contamination in recombinant ACT preparations. Villarino Romero et al used recombinant ACT but did not observe the same bacterial clearance as Betsou et al (19,31). ACT used by Cheung et al was highly purified of endotoxin (21), as was the RTX that we used in this study (9).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…An additional key aspect to consider is the potential endotoxin contamination in recombinant ACT preparations. Villarino Romero et al used recombinant ACT but did not observe the same bacterial clearance as Betsou et al (19,31). ACT used by Cheung et al was highly purified of endotoxin (21), as was the RTX that we used in this study (9).…”
Section: Discussionmentioning
confidence: 64%
“…Immunization with RTX alone does not enhance clearance of B. pertussis in CD-1 mice. ACT plays a key role in the pathogenesis of B. pertussis, and many studies have shown that both native and recombinant ACTs can be adjuvants and/or antigens for protection against pertussis in murine challenge studies (17)(18)(19)(20)(27)(28)(29)(30)(31). In this study, we aimed to systematically evaluate the RTX antigen (toxoid version of ACT, residues 751 to 1706) for inclusion into the acellular pertussis vaccine.…”
Section: Resultsmentioning
confidence: 99%
“…In mouse models, ACT-deficient bacteria are cleared faster than wild-type bacteria, and studies with immunodeficient and neutropenic mice suggest that ACT has a crucial role in enabling bacteria to resist neutrophil-mediated clearance 72, 73 . These data, in addition to the fact that ACT is one of the few virulence factors that is conserved and produced by all pathogenic Bordetella species 5 , suggest that ACT has the potential to be an effective antigen in future vaccine formulations 74 .…”
Section: Toxinsmentioning
confidence: 92%
“…Several T3SS proteins were found to be significantly downregulated in this study including Bsp22, BopN, BopD, and BteA. Bsp22 forms the T3SS tip complex, while BopD is a translocase for the T3SS effectors BteA and BopN ( Fennelly et al, 2008 ; Nagamatsu et al, 2009 ; Romero et al, 2013 ). Bsp22, BopN, and BopD were also previously found to be downregulated in the secretome in non-modulation conditions ( Luu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 64%